Flap monitoring with continuous oxygen partial tension measurement in breast reconstructive surgery: A preliminary report. Issue 4 (13th November 2017) - Trignano, Emilio; Fallico, Nefer; Fiorot, Luca; Bolletta, Alberto; Maffei, Matteo; Ciudad, Pedro; Maruccia, Michele; Chen, Hung‐Chi; Campus, Gian Vittorio
Abstract: Background: The best method for the postoperative monitoring of flaps in reconstructive surgery is still a matter of debate. The aim of this study is to evaluate the usefulness of an oxygen partial tension monitoring system for the postoperative follow‐up of a series of breast flaps, in addition to the traditional periodical clinical evaluations. Patients and Methods: Twenty‐one consecutive female patients (mean age: 61 years) who underwent free‐ or pedicled‐flap reconstruction of the breast were included in the study. Fifteen patients had a deep inferior epigastric perforator flap breast reconstruction, while the remaining six patients underwent a transverse rectus abdominus myocutaneous flap reconstruction. The Licox ® Recon (Integra LifeSciences Corp, Plainsboro, New Jersey) system was used for the monitoring of the flaps. The oxygen partial tension (PtO2 ) values were displayed on the system monitor and registered with appropriate software for statistical analysis. Results: A decreasing trend in the mean PtO2 values was observed over the first five postoperative days. The mean values registered in the first postoperative day were higher than those observed in the subsequent four days. Three patients were lost due to misplacement of the probe. Among the remaining 18 flaps, 3 (17%) reported a remarkable decrease in PtO2 values, with the mean PtO2 registered in the second postoperative day being significantly lower than in the other flaps (7.3 ± 0.7 vs. 17.0 ± 0.9; P ‐value <.05). These three flaps have been promptly re‐explored, with a final flap failure rate of 5.5% (1 flap). Conclusions: The continuous oxygen tension evaluation represents a promising method for the postoperative monitoring of breast reconstructive surgery flaps when used in combination with the traditional periodic clinical evaluations.